2003
DOI: 10.1034/j.1600-0536.2003.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

An audit of the value of patch testing and its effect on quality of life

Abstract: We have assessed the value of patch testing from the patient's perspective and examined the impact of patch testing on their quality of life (QoL). 140 patients were recruited over 5 months. 2 questionnaires were designed to investigate the patient's views on patch testing. The 1st questionnaire was completed at the final visit to the clinic and the 2nd was posted 6 weeks later. The Dermatology Life Quality Index (DLQI) questionnaire was completed on both occasions. There was a significant improvement of the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 12 publications
0
49
3
Order By: Relevance
“…Insufficient patients are being referred for patch testing in Yorkshire, yet despite this, most centres are still failing to see patients within an appropriate timescale. Delays in testing significantly affect quality of life and lengthen time off work for those with suspected occupational exposure …”
Section: Results Of the Auditmentioning
confidence: 99%
“…Insufficient patients are being referred for patch testing in Yorkshire, yet despite this, most centres are still failing to see patients within an appropriate timescale. Delays in testing significantly affect quality of life and lengthen time off work for those with suspected occupational exposure …”
Section: Results Of the Auditmentioning
confidence: 99%
“…This is also a time-consuming process, uncomfortable and can also cause reactions. Those studies showed that in spite of inconveniences most patients appeared to be satisfied with the procedure, especially when allergens were identified with the patch testing [13,14], that testing is perceived as a valuable tool by patients [13,14] and that patients would recommend patch testing to others [13]. Also in our study patients with positive DPT were actually more satisfied with the procedure than the ones with negative results, although this was not statistically different.…”
Section: Discussionmentioning
confidence: 99%
“…Patch testing is an objective and cost‐effective method used for the clinical work‐up of patients in whom allergic contact dermatitis is suspected or needs to be excluded . In addition, being patch tested because of suspected allergic contact dermatitis gives an improvement in quality of life (QoL) . Thomson et al.…”
mentioning
confidence: 99%
“…Woo et al. found that patch testing was beneficial for patients with positive and those with negative patch test results at a 6‐week follow‐up . On evaluation of QoL and time from patch testing, Hald et al.…”
mentioning
confidence: 99%